FOREIGN EXPERIENCE OF PATRIOTIC EDUCATION - Afanasieva Yu. V. (Pressing Problems of Public Administration, 2017)
The paper analyses the grounds of patriotic education in some countries of the world (the USA, GreatBritain, Germany, Lithuania, Latvia, Poland, Japan) according to the degree of state participation inthis process. It is determined that there is a direct link between patriotic education and the processof education in many countries. It is de ned that in the countries of Western Europe in the process ofdeveloping democratic lifestyle, patriotic education has transformed into formation of civicism, basedon the rights and freedoms of a person and citizen.